APPLYING GAMIFICATION (GAME ELEMENTS) TECHNOLOGY IN PHYSICAL EDUCATION LESSONS - Nazarov Nursultan Safarbayevich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the application of gamification technology in physical education lessons. It discusses how incorporating game elements, such as points, challenges, rewards, and interactive tasks, can increase student engagement, motivation, and learning outcomes. The paper highlights strategies for integrating gamification into various physical activities, emphasizing its potential to enhance physical fitness, teamwork, and overall participation. The study concludes that gamification not only makes lessons more enjoyable but also fosters long-term interest in physical activity and healthy lifestyle habits among students.